ENHANCING USER ENGAGEMENT IN DESA DIGITAL INDONESIA (DDI) KMS THROUGH GAMIFICATION DIGITAL NUDGES - Hutauruk, Dzakiyyah Hasbi; Nurhadryani, Yani; Mardiana, Rina (Pena Cendekia Insani, 2025)
This study examined how digital nudges integrated with gamification could improve user engagement in Desa Digital Indonesia (DDI) KMS. Using a user-centered design approach, the research was conducted in two iterative cycles involving user testing and interviews with 5 and 20 participants from rural backgrounds. An iterative process involving two design cycles was conducted, including user analysis, prototype development, and evaluation. The initial evaluation involved five participants and revealed that leaderboard and badge features were generally acceptable but less effective in collaborative contexts. Based on these findings, the design was refined by introducing collaborative elements and small incentives, including achievement titles and promotional rewards. The second evaluation showed improved user acceptance, with all participants preferring the new design, and the incentive-based feature receiving the highest positive rating (90%). The findings indicate that combining competitive, collaborative, and incentive-based nudges leads to more effective and contextually relevant user engagement in rural systems.